Analisa Evaluasi Program Gerakan Sadar Membayar Pajak dan Retribusi Melalui Pelayanan Masyarakat Terpadu (Gebyar Sipenyu) Tahun 2025 - Miranti Suci Puspitasari (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2025)
This study aims to evaluate the implementation of the Integrated Community Service Program for Tax and Retribution Awareness (Gebyar SiPenyu) in 2025, organized by the Regional Revenue Agency (Badan Pendapatan Daerah/BAPENDA) of Sukabumi Regency. The research employed a qualitative descriptive approach. Data were collected through observation, in-depth interviews, documentation, and literature review, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, supported by the CIPP (Context, Input, Process, Product) evaluation framework. The findings indicate that the Gebyar SiPenyu Program has been effective in improving regional tax service quality and optimizing Local Own-Source Revenue (Pendapatan Asli Daerah/PAD). The program’s effectiveness is reflected in the achievement of a 15.42% increase in regional tax and retribution revenues, exceeding the target of 6.74% with an achievement rate of 228.78%. In addition, regional tax revenue realization reached 100.01% of the target, while regional retribution revenue reached 102.74%. Service evaluation results reveal that most community members rated the program as good or very good, indicating a positive public response to the integrated and digital-based service innovations. However, several challenges remain, including uneven taxpayer compliance, limited human resources, the need for continuous updating of tax databases, and suboptimal integration of information systems. Therefore, strengthening service digitalization, enhancing human resource capacity, and improving tax data management are necessary to ensure the sustainability and effectiveness of the program in the future.